PELABELAN SELIMUT TOTAL SUPER (a,d)-H ANTIMAGIC PADA GRAPH LOBSTER BERATURAN L_n (q,r) - ROSALIA, TIRA CATUR; HARINI, LUH PUTU IDA; SARI, KARTIKA (E-Jurnal Matematika; Vol 6 No 2 (2017), 2017)
Graph labelling is a function that maps graph elements to positive integers. A covering of  graph  is  family subgraph from , for  with integer k. Graph  admits  covering if for every subgraph  is isomorphic to a graph  . A connected graph  is an - antimagic if there are positive integers  and bijective function  such that there are injective function , defined by   with . The purpose of this research is to determine a total super  antimagic covering on lobster graph . The method of this research is literature study method. It is obtained that there are a total super  antimagic covering for  on lobster graph  with integer and even number .